Cover Feature: Insights into Proton Dynamics in a Photofunctional Salt‐Cocrystal Continuum: Single‐Crystal X‐ray, Neutron Diffraction, and Hirshfeld Atom Refinement (Chem. Eur. J. 71/2021). Issue 71 (10th December 2021) - Yano, Yoshio; Ono, Toshikazu; Ohhara, Takashi; Hisaeda, Yoshio
Abstract : Hydrogen bonding is a fundamental interaction in daily life and plays an important role in chemical, physical, and biochemical processes. This work presents a metastable acid–base crystalline material whose luminescence color varies between green and yellow depending on the strength of the hydrogen bonds. The two single crystal structures shown were revealed in detail by neutron structural analysis and modern computational chemistry. More information can be found in the Full Paper by T. Ono, Y. Hisaeda, et al. (DOI: 10.1002/chem.202103044 ).